Virus-host systems in sea ice - Luhtanen, Anne-Mari (Helsingin yliopisto, 2017)
Virus-host systems in sea ice Sea ice is one of the largest habitats on Earth. A specialized microbial community lives inside the narrow brine channels that are formed during freezing process, when salt and other components from sea water concentrate between ice crystals. These microbes have an active role in the biogeochemistry of the sea ice by primary production, degradation of material and excreation of compounds, which effect the gas exchange between the ocean and atmosphere and the nutrient status of the under ice sea. Sea ice microbial community consist of auto- and heterotrophic protists, prokaryotes and viruses. The main heterotrophs are the bacteria. Viruses are the most abundant lifeform on Earth. They are found everywhere where there is life and they infect all kinds of cells. Infections are crucial for viruses because they can reproduce only by using a host cell to produce new virus particles. Majority of the viruses infect the most numerous cells on Earth, the prokaryotes, i.e. bacteria and archaea. Viruses infecting bacteria (bacteriophages or phages) are a major factor in bacterial mortality. They can also control the community composition of bacteria because of the high specificity of the infection. Bacteria have different mechanisms to avoid phage infections and phages need to evolve to be able to reproduce. This arms race of phages and bacteria can lead to co-evolution. Although viruses are known to have significant effects on bacterial communities in various habitats, not much is known about the viruses in the sea ice. Before this project, only three isolates have been reported from the Arctic sea ice. The aim in this thesis was to get a better understanding of the phages and their role in sea ice. For that, isolation, cultivation and purification methods needed to be developed and optimized. Bacteria and phages were isolated from samples taken from Baltic and Antarctic sea ice. The phage particles were purified and characterized by their morphology, structural protein patterns and host ...